Simultaneous effect of irradiance and temperature on biochemical composition of the microalga Pavlova lutheri - Carvalho, Ana P. (2010)
The biochemical composition of microalgae can be modulated through the environmental conditions prevailing during growth. The simultaneous effects of irradiance and temperature on the biochemical composition of Pavlova lutheri were evaluated using an experimental star factorial design. Five levels were tested for each parameter (temperature, 10, 14, 18, 22 and 26°C; irradiance, 60, 105, 150, 195 and 240 μmol photons m−2 s−1), whereas the carbohydrate, protein, lipid, pigments and elementary compound contents were measured as response variables. Additionally, in order to rapidly measure parameters to define the status of the culture, the validation of the relationships between biochemical parameters and physiological status were estimated through regression analysis. It was observed that irradiance and temperature play a major role in the determination of the biochemical composition of microalgae. Their effects are synergistic, and it can be observed that a trend in behaviour at a certain temperature can be reversed at a different temperature; therefore, when selecting the environmental conditions to a culture they must be studied in a combined fashion. Although there are consistent relationships between pigment contents and elementary compounds in cells, its linearity is influenced by the irradiance of the culture and its age; therefore, they can only be applied in specific circumstances. On the other side, population biomass was well estimated in terms of carotenoid content, irrespective of the environmental conditions provided and the growth phase.